PENERAPAN PENDEKATAN KONTEKSTUAL UNTUK MENINGKATKAN HASIL BELAJAR SISWA MATERI GEOMETRI BANGUN RUANG SISI LENGKUNG DI KELAS V SD INPRES BERTINGKAT KELAPA LIMA 1 - Salomi Debora Fallo (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Thesis by Salomi Debora Fallo, NIM 2101140104 Elementary SchoolTeacher Education Study Program in 2025, entitled “Application of ContextualApproach to Improve Student Learning Outcomes on Geometry of Curved SideSpaces in Class V SD Inpres Bertingkat Kelapa Lima 1”.This study aims to improve the learning outcomes of fifth grade students ofSD Inpres Bertingkat Kelapa Lima 1 through the application of a contextualapproach to the geometry of curved-sided spaces. The background of this study isthe low student learning outcomes on the geometry of curved-sided space and thelack of teacher creativity in the selection of approaches in the learning process.This research is a Classroom Action Research (PTK) which was carried out in twocycles, each consisting of planning stages, action implementation, observation andevaluation, and reflection. The research subjects were 24 students of class Vawith details of 11 male students and 13 female students. Data collectiontechniques used observation and tests.The results of this study prove that there is an increase in learningoutcomes from pre-cycle to cycle I, with a percentage of completeness of 16.7% (4students completed) increased to 58.3% (14 students completed), and in cycle IIincreased to 87.5% (21 students completed) of 24 students. Based on the resultsof this study, it can be concluded that the application of the contextual approachimproves student learning outcomes in the geometry of curved side space in classV SD Inpres Bertingkat Kelapa Lima 1.